Tradisi Nyadran Saat Pandemi Covid 19 Di Desa Tegalan Dk X Pedak, Kelurahan Trimurti, Kecamatan Srandakan, Kabupaten Bantul - Sa'adah, Umi; Sa'adah, Umi (Jurnal Dinamika Sosial Budaya, 2022)
This research was conducted to find out the nyadran tradition during the COVID-19 pandemic in Tegalan Village Dk X Pedak, Trimurti Village, Srandakan District, Bantul Regency. This research used a descriptive qualitative approach using a single embedded case study type of research. Sources of data obtained from sources and documentation.   The sampling technique was taken by purposive sampling technique.   Collecting data using interviews and documentation to find the validity of the data using source triangulation and method triangulation.   The data analysis technique uses an interactive analysis model. Based on the results of the study, it can be concluded that the nyadran tradition in Tegalan Village Dk X Pedak is a hereditary culture from ancient times which is a Javanese culture that is still preserved.   This tradition is important, this tradition is used to honor the ancestors as well as a form of gratitude and forgiveness for the ancestors.   Nyadran comes from the Hindu-Buddhist tradition.   Since the 15th century the Walisongo combined this tradition with their da'wah, so that Islam could be easily accepted.   Activities carried out by the community in the village of Tegalan Dk X Pedak are usually the day before the implementation of the nyadran tradition, the villagers work together to clean the graves and the tomb environment.   Then in the evening held muqodaman (recitation of the Qur'an 30 Juz) and recitation and remembrance of tahlil sending prayers for the ancestors.   On the day of the event, a ritual prior to the COVID-19 pandemic was held by making offerings, the village residents gathered on the terrace of the tomb.   The offerings and thanksgiving feasts are contained and each umbarampe used has its own philosophical meaning.   This nyadran tradition has many cultural and educational values so it needs to be preserved so that it does not become extinct and the younger generation can continue it.  ABSTRAK  Penelitian ini dilakukan untuk mengetahui tradisi nyadran pada saat pandemi covid 19 di Desa Tegalan Dk X Pedak. Penellitian ini menggunakan pendekatan deskriptif kualitatif, jenis penelitian studi kasus tungal terpancang. Sumber data diperoleh dari narasumber dan dokumentasi. Teknik sampling diambil dengan Teknik purposive sampling. Pengumpulan data menggunakan wawancara dan dokumentasi untuk mencari validitas data menggunakan trianggulasi sumber dan trianggulasi metode. Teknik analisis data menggunakan model analisis interaktif. Berdasarkan hasil penelitian disimpulkan bahwa tradisi nyadran di Desa Tegalan Dk X Pedak merupakan budaya turun-temurun dari zaman dahulu. Tradisi ini digunakan untuk menghormati leluhur, wujud syukur dan permohonan ampun untuk leluhur. Sejak abad ke-15 Walisongo menggabungkan tradisi dengan dakwahnya, agar agama Islam dapat mudah diterima. Aktivitas masyarakat Desa Tegalan sehari sebelum pelaksanaan tradisi nyadran warga desa bergotong-royong membersihkan makam. Malam harinya diadakan muqodaman (pembacaan Al-Quran 30 Juz), pengajian, dzikir tahlil, doa untuk leluhur. Pada hari acara sebelum adanya pandemi covid 19 diadakan dengan membuat sesaji, keduri warga desa berkumpul di teras makam.. Tradisi nyadran ini terdapat nilai budaya maupun Pendidikan sehingga perlu dilestarikan.
Keywords: Tradisi; Budaya; pendidikan